Finite Element Analysis of the Geogrid-Pile Foundation System under Earthquake Loading - Ghanim, Athraa A. Al; Shafiqu, Qassun S. Mohammed; Ibraheem, Asma Thamir (Al-Nahrain Journal for Engineering Sciences, 2019)
The finite element method is one of the important methods in analyzing geotechnical engineering problems; its main advantage is the ability to apply for the materials exhibiting non-linear stress-strain behavior. In this study the finite element program PLAXIS 3D 2013 is used to study the behavior of the piles under the influence of seismic waves in saturated sandy soil and the effect of adding geogrid with the pile foundation. The program has been used to facilitate the representation of the real model, input the required soil parameters and implementation of seismic data. Seismic wave, the soil geometry and the pile dimensions were fixed in all models, while dimension and depth of the geogrid used were varied to study the influence of different depth and dimension in reducing the pile displacements and the pore water pressure of soil. The results show that The reduction in settlement ratio (the difference between settlement of pile without and with using geogrid to the settlement without using geogrid) for ( ×L/2), (L×L) and (2L×2L) are 10.6%, 17% and 21.3% respectively. And the settlement ratio for geogrid at depths 8.33% and 12.5% of pile length are 9.6% and 17% respectively.